Morphological and morph metric study of the mandible in the local Rabbits (Oryctolagus Cunicuius) - Salih, Qismah Modhafar (The Iraqi Journal of Veterinary Medicine, 2016)
Eleven adult local rabbits (6 female and 5male) were used for this study. The mandible were prepared to study the gross anatomical features. The main gross characteristics feature of the local rabbits mandible the ramus forms a broad, thin and flat plate, the surface of the ramus is greatly increased in its posteroventral portion to form the angle or angular process. The articular surface is elongated and carry on its caudodorsal end a slightly oblique condyloid process, this process in rabbit is raised much above the planes of the molar table and has a prolonged aspect in a longitudinal plan. In front of the shallow mandibular notch, the coronoid process is short and blunt process situated in front of mandibular notch. In the rabbit mandible the alveoli for the canine teeth were absent resulting in a large diastema Mandibular foramen situated on the medial surface immediately behind the last molar. There is a large retroalveolr foramen. The female local rabbit showed significant greater measurement than the male.